An apparatus for the active thermal testing of corrosion in steel cylindrical containers and test results; Russian Journal of Nondestructive Testing; Vol. 49, iss. 11 - Vavilov V. P. Vladimir Platonovich; Nesteruk D. A. Denis Alekseevich; Chulkov A. O. Arseniy Olegovich; Shiryaev V. V. Vladimir Vasilyevich (2013, 2013)
Title screen